2008
DOI: 10.1002/sce.20286
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of argumentation and explanation

Abstract: ABSTRACT:Constructing scientific explanations and participating in argumentative discourse are seen as essential practices of scientific inquiry (e.g., R. Driver, P. Newton, & J. Osborne, 2000). In this paper, we identify three goals of engaging in these related scientific practices: (1) sensemaking, (2) articulating, and (3) persuading. We propose using these goals to understand student engagement with these practices, and to design instructional interventions to support students. Thus, we use this framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
456
1
24

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(492 citation statements)
references
References 40 publications
11
456
1
24
Order By: Relevance
“…Therefore, it emerged that when the students participate (with regard to their verbalized knowledge and actions) similarly and the work is carried out collectively by all the members of the group, then they tend to formulate statements combining the used apparatus and materials with chemistry concepts. This link is both an essential objective of the labwork and a finding in line with research results which showed that the active and similar participation of the students in the discourse promotes dialogical argumentation and the construction of concepts by them (Berland & Reiser, 2009;Engle & Conant, 2002;Osborne, Erduran, & Simon, 2004;Sampson, 2009).…”
Section: Discussionsupporting
confidence: 69%
“…Therefore, it emerged that when the students participate (with regard to their verbalized knowledge and actions) similarly and the work is carried out collectively by all the members of the group, then they tend to formulate statements combining the used apparatus and materials with chemistry concepts. This link is both an essential objective of the labwork and a finding in line with research results which showed that the active and similar participation of the students in the discourse promotes dialogical argumentation and the construction of concepts by them (Berland & Reiser, 2009;Engle & Conant, 2002;Osborne, Erduran, & Simon, 2004;Sampson, 2009).…”
Section: Discussionsupporting
confidence: 69%
“…Thus, we suggest that the students' various ways of legitimizing 6 one another's disparate ideas (in this case, making concessions and maintaining two competing ideas) enabled all students to be perceived as competent in their discussions. This sense of competency made it acceptable for the students to be wrong and revise their thinking even in the face of the typical school goal of demonstrating individual success (Johnson & Johnson, 1994), and the argumentative goal of being persuasive (Berland & Reiser, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Berland and Reiser (2009; depict scientific argumentation as the negotiation of two goals-sensemaking and persuasion. Or, as depicted by Ford (2008), argumentation requires two roles-knowledge constructor and knowledge critic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark & Sampson, 2006;Osborne, Erduran, Simon, 2004;Sandoval & Reiser, 2004) for teachers to teach science through argumentation. Supporters of argumentation in science classrooms maintain that the implementation of these curriculum materials or instructional strategies advocated in current science education literature requires knowledgeable teachers that understand the theoretical assumptions underpinning scientific argumentation, value argumentation-based teaching as a way to promote meaningful learning in their classrooms and hold practical knowledge and skills to teach science through argumentation (Berland & Reiser, 2009;Erduran, Ardac, Yakmaci-Guzel, 2006;Knight & McNeill, 2011;Kuhn, 2010;McNeill et al, 2006;McNeill, 2009;Osborne, Simon, Howell-Richardson, Christodoulou, 2010;Sampson, 2009). As Erduran et al (2006, p.3) state, "the execution of argumentation in real science classroom will demand more than rhetoric".…”
mentioning
confidence: 99%